Effect the Grain Size on the Polymer Matrix Composites Reinforced by Reenia Particles - A.hassan, Mohammed A sadik; Sallal, Hayder Abbas; kahlol, Kdhim khaion (Al-Khwarizmi Engineering Journal, 2013)
Synthetic polymers such as polyurethane are used widely in the field of biomedical applications such as implants or part of implant systems. This paper focuses on the preparation of base polymer matrix composite materials by (Hand Lay-Up) method, and studying the effect of selected grain size (32, 53, 63, 75, and 90) µm of (Reenia) particles on some properties of the prepared composite. Mechanical tests were used to evaluate the prepared system (Tensile, Compression, Impact, and Hardness) tests, and a physical test of (Water absorption %), and all tests were accomplished at room temperature. Where results showed tensile test (maximum tensile strength and modulus of elasticity) high at small grain size while the percentage of elongation decreased with increasing size. As the compressive strength increased with small grain size. And also the values of hardness and fracture energy affected by particle size where the hardness and fracture energy increased at small particles size of compared to larger particles size. While the percentage of water absorption increased at large particle size. In general the results showed clear improvement in properties and maximum values which get it of tensile strength, Modulus of elasticity, elongation percentage, compression strength, fracture energy, hardness and water absorption were as follows ((34.8 MPa), (10%), (268 N/mm2), ( 54.2 MPa),( o.408 J), (78.9 Shor (D)), (0.2668 %)) at using (32µm)) except water absorption was at (90µm) .